An empirical kinetic approach to study the occurence of ion exchange between counterions (X/Y) at the cationic micellar surface / Norazizah Abd Razak - Norazizah , Abd Razak (2018)
In this study, the values of Br X R (relative CTABr micellar binding constants of counterions X- and Br-) for different counterion Xν- (ν = 1, 2) were determined by a semiempirical kinetic (SEK) and spectrophotometric (SESp) methods. In SEK method, the effects of [MνX] on pseudo-first-order rate constants (kobs) for piperidinolysis of phenyl salicylate (PSa-), in the presence of constant concentration of cetyltrimethylammonium bromide [CTABr]T or didodecyldimethylammonium bromide [DDABr]T and [NaOH], were studied. For SESp technique, the effects of [MνX] on the initial absorbance (Aob) values of samples containing constant concentration of N-2-methoxyphenylphtalamic acid (N-2-MeOPhPTH), [CTABr]T and [NaOH] were obtained at 310 nm and 35 °C. The values of 0S K , for S- representing PSa-, were determined as (18.7 × 103) M-1 and (33.7 × 103) M-1 in the presence of respective wormlike micelles (WM) and vesicles (Vs). The value of 0S K , for S- representing N-2-MeOPhPT-, at 35 °C is 3624 M-1. The mean values of Br X R for Xν- representing (i) 3- and 4-methylsalicylate (3-, 4-MeSaν-) at 35, 40, 45 and 55 °C are > 1.5 – 1.9-fold larger than those of 4-methoxysalicylate (4-MeOSaν-); (ii) aliphatic carboxylate groups at 35 °C are 0.31, 0.56, 0.77, 1.88, 15.3 and 74.3, for respective CH3COO-, C2H5COO-, C3H7COO-, C4H9COO-, C6H13COO- and C7H15COO-. The break in the plots of kobs versus [MνX] reveals that the micellar binding of counterion X has initiated the morphological transformation of micelles’ structure. Rheological flow measurements of aqueous 15 mM CTABr and different [MνX] solutions revealed the presence of WM or Vs due to observable shear thinning behavior and the presence of maxima in the plot of zero shear viscosity, η0 versus [MνX]. The values of η0, critical shear rate, cr γ as well as flow activation energy parameters, show a quantitative correlation between counterion (Xν-) binding affinity to cationic micelles and Xν--induced micellar growth. The presence of turbidity maximum in the plot of corrected absorbance, Aob versus [MνX] indirectly shows the presence of Vs in the aqueous system.